Dopingless super‐steep impact ionisation MOS (dopingless‐IMOS) based on work‐function engineering. Issue 12 (1st June 2014) - Singh, S.; Kondekar, P.N.
Abstract : A unique approach is proposed to realise dopingless impact‐ionisation MOS (dopingless‐IMOS) using work‐function engineering of electrodes to form charge plasma as a substitute for doping. Using appropriate work‐function difference between metal electrodes and intrinsic silicon film with thickness less than the intrinsic Debye length ( L D ) leads to charge plasma formation, in turn this charge plasma induces uniform p ‐type source and n ‐type drain. The proposed dopingless‐IMOS is simulated using two‐dimensional technology computer‐aided design (TCAD) Sentaurus to compare its electrical characteristics with conventional IMOS having identical device dimensions and bias conditions. Dopingless‐IMOS (DL‐IMOS) offers a simple fabrication process flow as it avoids the need for ion implantation, photo masking and complicated thermal budget. Hence, it is highly immune to process variations, doping control issues and random dopant fluctuations and it retains the inherent distinctive advantages of IMOS.